Quantifying the impacts of artificial flooding as a salt interception measure on a river-floodplain interaction in a semi-arid saline floodplain. (May 2016) - Alaghmand, S.; Beecham, S.; Woods, J.A.; Holland, K.L.; Jolly, I.D.; Hassanli, A.; Nouri, H.
Abstract: The natural flow regime of the Lower Murray River in South Australia has been altered and resulted in severe decline in the condition of long-lived vegetation on the floodplain. This paper aims to quantify the relative impacts of artificial flooding on the flow and solute dynamics of the floodplain aquifer and its ecological implications. It is shown that artificial flooding can temporarily form less saline groundwater and soil profiles which in turn improves water availability for vegetation. From ecological point of view, artificial flooding delivers some of the same benefits as natural overbank floods. However, the washed-off solute mass from the soil profile was only sustained for 4–6 months. It appears that artificial flooding is an intervention technique that is limited spatially to the flooded area and temporally to the flood duration. Hence, it may be considered as a short term management technique in arid and semi-arid areas. Highlights: We quantified impacts of artificial flooding on saline floodplain and its ecological implications. Combination of artificial flooding and groundwater lowering resulted in a 4% decrease in solute mass. Groundwater discharges to the river following artificial flooding cannot increase river salinity. Artificial flooding can temporarily form less saline groundwater and soil profiles that improve water availability. Artificial flooding may be considered as a short term management technique and needs to be applied periodically.